PENGARUH WORK FAMILY CONFLICT TERHADAP STRES KERJA DAN KINERJA WANITA PERAWAT DI RUMAH SAKIT UMUM DAERAH PRAYA LOMBOK - Agustina, Reny; Sudibya, I Gde Adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.03.TAHUN 2018, 2018)
Work Family Conflict is one of the most frequent conflicts among nurses in married nurses, where a nurse has to divide the time for business and household. If workplace family conflicts can not be avoided, then it can cause stress and performance. While the performance is much needed in the job as a nurse, which must be infected patients with high risk. The purpose of this study is analyze the effect of family conflict on job stress and performance. The research conducted at Praya Hospital. The number of samples study is 49 respondents with purposive sampling method with the criteria of female nurses who are married. Data with questionnaire distribution and using Path Analysis as data analysis techniques. The Sobel test is also used to determine whether there is mediation. The results of this study indicate that family conflict has a positive effect on job stress, work stress negatively affect the performance, and work family conflict negatively affect the performance,work stress is mediate the influence of conflict family on performance. Practical implications of this research are expected to be a consideration for the management of Praya Hospital to better pay attention to the welfare of nurses who experience family conflicts so as to reduce stress levels and improve the performance of nurses.